Classification of Ear Diseases In Siddha Literatures - A Review - Thayalini, T.; Sinthu, y.; Ragavan, A. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Siddha medicine is one of the medical systems of Sri Lanka. In Siddha medicine, Ear diseases are described under the Siroroga maruthuvam. The classification of the ear diseases are verify in literature to literature. The aim of the study is to review the classification of ear diseases in Siddha Literatures. Pararajaserkaram Siroroganethanam, Siddhar Aruvaimaruthuvam, Thanvanthirivaithiyam (Part one), Yukimuni Vaithiya Sinthamani, and Sarabentheravaithiyamuraikal Siroroganithanam were selected for this study. These were obtained from the library, Unit of Siddha Medicine, University of Jaffna. The data were collected from these literatures and analyzed. From the review, eighty one types of ear diseases were identified. Out of 81 types, 55 (68%) diseases were mentioned in the books of Pararajasekaram Siroroganithanam and Siddhar Aruvaimaruthuvam, 24 (30%) diseases in the book of Sarabenthiravithiyam, and 2 (2%) diseases in Yookimunivaithiya Chinthamani. Only 5 types are mentioned in Thanvanthirivaithiyam these types are included in the book "Sarabenthiravaithiyamuraik!". Among the 55 types, Karapan (8), Kuddam (8), Paru (8), Vitpuruthi (6), Elutchee (6), Soolai (6), Pilavai (5), Vatham (4) and Sanni (4) were included. This study shows that the classifications of diseases were made based on the character of discharge, colour of the pigment, and elevation of the skin of the ear. Some types were classified according to the formation of the abscess on the muscle, bone of the ear. According to the Siddha literature ear diseases were classified based on the signs and symptoms.
Keywords: Ear diseases; Classification; Siddha literatures